Interpersonal communication - Floyd, Kory (McGraw-Hill Education, 2021)
"Interpersonal Communication 4e help students to see how communication not only affects their relationships but also influences their health, happiness, and quality of life. It encourages students to go beyond commonsense notions about communication and help them see the value of investigating interpersonal processes-both face-to-face and online-in a systematic way."--Provided by publisher.